THE EFFECTS OF ACTIVITY - BASED LEARNING AND METACOGNITIVE ACTIVITIES ON MATHEMATICAL REASONING ABILITY OF MATHAYOMSUKSA III STUDENTS ON PROBABILITY - Suwannachairob, Wanwisa; Somchaipeng, Tongta; Chuntra, Chanon (Journal of MCU Nakhondhat, 2021)
The Objectives of this research article were to study the effects of activity - based learning and metacognitive activities on mathematical reasoning ability of probability of Mathayomsuksa III students. The sample was 35 Mathayomsuksa III, Prainsuksa Klomsakul U - tid School students in the second semester of the academic year 2019. They were randomly selected by using cluster random sampling, one classroom of four classrooms. The instruments were 11 lesson plans on activity - based learning and metacognitive activities on probability, and the Mathematical reasoning Ability Test on probability. The data were statistically analyzed by using percentage, mean, standard deviation and one sample T - Test. The result revealed that mathematical reasoning ability of Mathayomsuksa III students on probability using active - based learning and metacognitive activities was higher than the determined criterion 70 percent of the total scores with statistically significant at .05 level. Afterward, we using activity - based learning and metacognitive activities, Students have score average for mathematical reasoning was 15.14 or 75.70%. Passed the criteria 70 percent of 26 people or 74.29 % and did not meet the criteria of 9 people or 25.71 %.